ANALISA ANTOSIANIN PADA SEDIAAN MINUMAN EFFERVESCENT SARI BUNGA TELANG (Clitoria ternatea) DAN JERUK RIMAU GERGA LEBONG (Citrus nobilis sp.) MENGGUNKAN METODE pH DIFERENSIAL - lina, Herlina; Herlina; Mulyani, Elly; Anlika, Rindi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Anthocyanin is a compound that forms natural dyes in plants to give color.Telang flowers are one of the plants that contain anthocyanin compounds that arebeneficial for health in the body and swallowed flowers can also be made in practicaldosage forms, such as effervescent drink preparations. This effervescent drink is alsocombined with gerga lebong lime which will produce a fresher taste. This study aims todetermine the content of anthocyanin compounds in processed effervescent drinks. In thisstudy, the identification of anthocyanins in effervescent beverage preparations, telangflower juice and oranges gerga lebong using qualitative test methods using HCl 2M andNaOH 2M reagents, while in quantitative tests using UV-Vis spectrophotometry,differential pH method with pH 1.0 and pH 4.5 solutions at wavelengths of 510 nm and700 nm. The results of the qualitative test showed that all samples of processedeffervescent drinks were positive for anthocyanins and the quantitative test resultsshowed that the anthocyanin levels in formulation 1 were 1,780 mg / L, formulation 2 was2,225 mg / L, and formulation 3 was 5,899 mg / L. Based on this study on effervescentbeverage formulation 3 had high anthocyanins from formulations 1 and 2.